Some N-(5-methyl-1,3,4-thiadiazol-2-yl)-4-[(3-substituted)ureido/thioureido]benzenesulfonamides as carbonic anhydrase I and II Inhibitors - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH; KARAKUŞ, SEVGİ; TÜRK, SEVDA (MARMARA UNIV, FAC PHARMACY, 2016)
In the present study, N-(5-methyl-1,3,4-thiadiazol-2-yl)-4-[(3-substituted)ureido]benzenesulfonamide (1-9) and N-(5-methyl-1,3,4-thiadiazol-2-yl)-4-[(3-substituted) thioureido]benzenesulfonamide (10-14) derivatives were synthesized from 4-amino-N-(5-methyl-1,3,4-thiadiazol-2-yl) benzenesulfonamide (sulfamethizole). All new compounds were characterized by elemental analysis and various spectroscopic methods (FTIR, H-1-NMR and MS). These new sulfonamide derivatives were investigated as inhibitors of carbonic anhydrase especially human carbonic anhydrase I and II. The new compounds showed higher activity against the human cytosolic CA I (IC50 values 0.144-15.65 nM) and CA II (IC50 values 0.109-17.95 nM) in comparison with the clinically used CA inhibitor acetazolamide.
Keywords: Carbonic anhydrase inhibitors; sulfonamide; sulfamethizole; urea and thiourea; PURIFICATION; XII